2011
DOI: 10.1891/1058-1243.20.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Grand Multiparous Women’s Perceptions of Birthing, Nursing Care, and Childbirth Technology

Abstract: This qualitative descriptive study explored grand multiparous women's perceptions of the evolving changes in birthing, nursing care, and technology. A purposive sample of grand multiparous women (N 5 13) from rural, eastern Washington State were interviewed as they shared their 105 birth stories. Eight themes were identified: (1) providing welcome care, (2) offering choices, (3) following birth plans, (4) establishing trust and rapport, (5) being an advocate, (6) providing reassurance and support, (7) relying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Women in our study also viewed such relationships as contributing to the effective monitoring of their pregnancies. Primiparous women were more likely to identify the importance of relationship during pregnancy (Dahlen et al, 2008); multiparous women emphasised the importance of these relationships continuing across pregnancies, particularly for women with a complex pregnancy history (Fleming et al, 2011). A woman's desire for continuity across pregnancies is a likely extension of wanting relational aspects and systems of care continuity including good communication within the system, health providers and consistent policies (Green et al, 2000;Haggerty et al, 2003;Lees G, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Women in our study also viewed such relationships as contributing to the effective monitoring of their pregnancies. Primiparous women were more likely to identify the importance of relationship during pregnancy (Dahlen et al, 2008); multiparous women emphasised the importance of these relationships continuing across pregnancies, particularly for women with a complex pregnancy history (Fleming et al, 2011). A woman's desire for continuity across pregnancies is a likely extension of wanting relational aspects and systems of care continuity including good communication within the system, health providers and consistent policies (Green et al, 2000;Haggerty et al, 2003;Lees G, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Divergent perceptions and priorities may lead to confl ict between caregivers and patients. Patients may feel unsupported because nurses and doctors may focus more on technology rather than face-to-face patient care (Fleming et al, 2011). Nurses and doctors may become frustrated because patients come into the hospital with a list of expectations, but have not prepared emotionally or physically for their birth (Carlton et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Declercq et al (2006) reported that, although women recognized their right to informed consent and informed refusal, 73% of women who had episiotomies were not given a choice in this decision. Research shows that women consistently expressed a desire for information to exercise their autonomy (Carlton et al, 2005;Fleming et al, 2011;Helk et al, 2008;Lothian, 2010;Yam et al, 2007). The birth plan is one tool that can be Declercq et al (2006) reported that, although women recognized their right to informed consent and informed refusal, 73% of women who had episiotomies were not given a choice in this decision.…”
Section: Ethical Implicationsmentioning
confidence: 99%
“…Participants focused on the importance of providers establishing trust and rapport as well as providing reassurance and support versus relying on childbirth technology in the provision of care (Fleming, Smart, & Eide, 2011).…”
Section: Discussionmentioning
confidence: 99%